Development of Finger Clubbing Meter - Masra, S.M.W.; Goh, K.L.; Henry, J.S.; Muhammad, M.S.; Djojodibroto, R.D.; Sapawi, R. (Trans Tech Publications, Switzerland, 2016)
Finger clubbing, also known as drumstick finger, is the medical symptom that is indicated by the development of the sponginess or swelling in the nail beds of nails and toes. The higher grade of clubbing on the patients can be easily identified with the presence of drumstick finger. The existing available measurement device to identify the early stage of clubbing required much time which is impractical for a busy clinic practice. This paper explains the determination of the finger clubbing by using the Digital Index (DI) measurement, which was deployed by implementing and developing the Portable Finger Clubbing Meter hardware and the Microsoft Visual Basic (VB) Graphical User Interface (GUI). Finger circumference values of nail-fold (NF) and distal interphalangeal joint (DIP) of twenty participants were measured using the developed hardware. Data analysis was then performed using the GUI for DI computation, and the presence of finger clubbing could be determined.